Lack of lymphocytes impairs macrophage polarization and angiogenesis in diabetic wound healing - Seraphim, Patricia M. [UNESP]; Leal, Ermelindo C.; Moura, João; Gonçalves, Pedro; Gonçalves, Jenifer P.; Carvalho, Eugénia (Elsevier, 2020)
AIMS: This study aimed to investigate the effect of lymphocytes in wound healing and the underlying mechanisms, in diabetic and non-diabetic mice, using Balb/c recombination activating gene (Rag)-2 and interleukin 2 receptor gamma (IL-2Rγ) double knockout (KO) (RAG2−/− IL-2Rγ−/−) mice. MAIN METHODS: Wound healing in vivo was performed in control and STZ-induced diabetic mice, in both KO and WT mice. Inflammation and ROS production were evaluated by immunofluorescence microscopy analysis, antioxidant enzymes and angiogenesis were evaluated by quantitative PCR and immunofluorescence microscopy analysis, and wound closure kinetics evolution was evaluated by measurement of acetate tracing of the wound area. KEY FINDINGS: Wound closure was significantly delayed in KO mice, where the M1/M2 macrophage ratio and basal ROS levels were significantly increased, while antioxidant defenses and angiogenesis were significantly decreased. Moreover, the expected increase in matrix metallopeptidase (MMP)-9 protein levels in diabetic conditions was not observed in KO mice, suggesting that the mechanisms leading to the increase in MMP-9 observed in diabetic wounds may in part be lymphocyte-dependent. SIGNIFICANCE: Our results indicate that lack of lymphocytes compromises wound healing independent of diabetes. The lack of these cells, even in non-diabetic mice, mimics the phenotype observed in wounds under diabetic conditions. Moreover, the combination of diabetes and the lack of lymphocytes, further impair the wound healing conditions, indicating that when the innate regulatory function is lost in these KO mice, excessive M1 polarization, poor angiogenesis and impaired wound healing are worsen.
Keywords: Diabetes; Inflammation; Lymphocytes; Reactive oxygen species; Wound healing